2019
DOI: 10.1016/j.ocemod.2019.101423
|View full text |Cite
|
Sign up to set email alerts
|

On the implementation and consequences of the oceanic currents feedback in ocean–atmosphere coupled models

Abstract: The Current FeedBack (CFB) to the atmosphere simply represents the influence of the surface oceanic currents on near-surface wind and surface stress. As the CFB has a significant influence on the oceanic circulation, it is crucial to implement it properly in a coupled Ocean-Atmosphere model. In this study, we first detail the modifications to be implemented into atmospheric models to account for the CFB. In the computation of air-sea fluxes, the relative winds, i.e., the difference between the near-surface win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Note that to properly take into account the impact of the oceanic surface current in the atmosphere, we must also modify the tridiagonal matrix system solved in the vertical turbulent diffusion scheme (Lemarié, 2015;Renault, Lemarié, & Arsouze, 2019).…”
Section: Surface Wind and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that to properly take into account the impact of the oceanic surface current in the atmosphere, we must also modify the tridiagonal matrix system solved in the vertical turbulent diffusion scheme (Lemarié, 2015;Renault, Lemarié, & Arsouze, 2019).…”
Section: Surface Wind and Stressmentioning
confidence: 99%
“…When estimating the surface stress in a coupled model, the CFB is taken into account by using the wind relative to the oceanic current instead of the absolute wind neglecting surface motion (Renault et al, ). From an oceanic perspective, coupled simulations are computationally expensive because of the high computational cost of atmospheric models with respect to oceanic ones.…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al, 2016;Seo, 2017;Renault et al, 2016;Jullien et al, 2020). Renault et al (2017Renault et al ( , 2019 showed a damping of the eddy kinetic energy due to the current feedback modulation of the energy transfer between the ocean and the atmosphere leading to more realistic simulations. These current-wind interactions need to be further investigated in our coupled system with the insertion of the current terms in the AROME turbulence scheme.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the current feedback is concerned, Renault et al (2016b) showed that the reduction of wind power input to the ocean is systematically overestimated in oceanic simulations based on an ASL forcing strategy compared to air-sea coupled simulations. A simulation that neglects the MABL adjustment to the current feedback cannot represent the partial re-energization of the ocean by the atmosphere and hence overestimates the drag effect by more than 30 % (e.g., Renault et al, 2016bRenault et al, , 2019a. The ASL forcing strategy used in most oceanic models will thus overestimate the current feedback effect and underestimate the downward momentum mixing.…”
Section: Air-sea Interactions At Oceanic Mesoscalesmentioning
confidence: 99%